Zinc exerts its renal protection effect on arsenic-exposed common carp: A signaling network comprising Nrf2, NF-κB and MAPK pathways. Issue 104 (September 2020) - Wang, Yu; Zhao, Hongjing; Liu, Yachen; Nie, XiaoPan; Xing, Mingwei
Abstract: Epidemiological and laboratory investigations have extensively indicated that arsenic exposure accounts for several kidney diseases. Zinc has been suggested as a possible natural preventive and therapeutic agent. This study is designed to explore the beneficial effect of zinc supplementation against arsenic-induced renal toxicity in common carp, and the results point to signaling pathway possibly compromised. In the present study, renal injury was induced in common carp by waterborne exposure to arsenic (2.83 mg/L) for 30 days, and zinc (1 mg/L) was simultaneously supplemented. First, the arsenic-exposed fish showed histological and functional renal alterations (indicated by hematoxylin-eosin staining, biochemical indexes and a TUNEL assay). Moreover, as a reactive oxygen species (ROS) stimulant, arsenic was found to induce oxidative toxicity as determined by increased renal ROS, malondialdehyde, protein carbonyl and 8-hydroxydeoxyguanosine levels. When antioxidant-mediation attempts (through superoxide dismutase and glutathione)-mediated to restore homeostasis failed and ROS increased to extreme levels, inflammation (indicated by elevated inducible nitric oxide synthetase, tumor necrosis factor-alpha and interleukins levels) and apoptosis (through both mitochondrial- and death receptor-dependent pathways) were triggered. However, abnormalities in the upstream mediators Nrf2, NF-κB and MAPK were significantly ameliorated and blocked by treatment with zinc. In conclusion, zinc exerts a substantial protective effect against arsenic-triggered subchronic renal injury in common carp via the amelioration of oxidative stress, suppression of apoptosis and reduced inflammation through Nrf2, NF-κB and MAPK signaling. Graphical abstract: Image 1 Highlights: Arsenic's oxidative toxicity elicits inflammation and apoptosis in kidney. Zinc recovers arsenic-induced renal histological and functional alterations. Zinc relieves arseniasis via Nrf2/NF-κB/MAPK pathways.